Pengaruh Regenerasi Kota Terhadap Kualitas Lingkungan Permukiman Industri Kecil Batik Studi Kasus: Kawasan Pabean, Kota Pekalongan - Hari Sucahyo; Wisnu Pradoto (Universitas Islam Sultan Agung Semarang, 2020)
The development of Pekalongan city is rapidly due to its strategic location in the northern coast of Java and the establishment of a world heritage of Batik, so that it gives an influence on all aspects, especially social and economic. Pabean as one of the centers of the home-based batik industry in Pekalongan also played a role in the development of batik, but the existence of the tidal disaster coupled with the lack of conscious entrepreneurs in waste processing has made settlements at customs in a declining environmental quality. Regional recovery programs have been present with the aim of returning the function of settlement infrastructure and facilities in Pabean. This study seeks to examine how much influence the urban regeneration has on the quality of the residential environment in Pabean. by using multiple linear regression analysis using three independent variables which are the concept of urban regeneration, namely social relations of the community, participation of the private sector and the government in maintaining environmental quality, and the relationship between the public and private sector and the government towards the dependent variable of the quality of the settlement environment is obtained by the effect of 14, 29 percent.Keywords: urban regeneration, pekalongan, batik, Pabean